Pengabdian Kepada Masyarakat (PKM) Penggunaan Terapi Uap dengan Aromaterapi Minyak Kayu Putih (Eucalyptus Oil) Pada Anak dengan Infeksi Saluran Pernafasan Akut (ISPA) Di RT 01 Kelurahan Batu Urip Kota Lubuklinggau - Ningsih, Widya Aprilia; Meiria, Eni; Zulfiana, Melingga; Pratiwi, Iing; Martini, Lovi; Rossita, Taufianie (Jurnal Dehasen Mengabdi, 2024)
ARI is still the main cause of morbidity and mortality from infectious diseases in the world. According to 2020 World Health Organization (WHO) data, it is known that there were 1,988 cases of ISPA in toddlers aged 1-5 years with a prevalence of 42.91%. In Indonesia, ARI always ranks as the first cause of death in infants and toddlers. ISPA also often occupies the list of the 10 most common diseases in hospitals and health centers. ISPA disease in developing countries accounts for 25% of deaths in children, especially babies aged less than two months. Indonesia is one of the developing countries with the highest number of ISPA cases. Data from 2021-2023, ISPA continues to increase and has reached 200 thousand cases. According to data from the Megang Community Health Center, it was found that the number of toddlers suffering from ISPA in 2023 was 522 children (Megang Health Center Profile, 2023). Based on these problems, the author chose to provide counseling regarding ISPA and a demonstration of steam therapy with eucalyptus oil aromatherapy as an alternative for treating ISPA, especially in toddlers. The outreach and demonstration activities were carried out directly at RT 01, Batu Urip Village, Lubuklinggau City, attended by 31 mothers of toddlers, cadres, sub-district midwives and field CIs. Residents who attended were active and cooperative in the outreach program and demonstration of steam therapy using eucalyptus oil aromatherapy. The participants participated in the extension and demonstration activities actively and enthusiastically, as evidenced by the many participants who asked and answered questions from the extension officers during the question and answer and discussion sessions. After the activity is finished, it is closed by completing the posttest by the participants.